2018
DOI: 10.1093/llc/fqy005
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering gender bias in newspaper coverage of Irish politicians using machine learning

Abstract: This paper presents research uncovering systematic gender bias in the representation of political leaders in the media, using artificial intelligence. Newspaper coverage of Irish ministers over a fifteen year period was gathered and analysed with natural language processing techniques and machine learning. Findings demonstrate evidence of gender bias in the portrayal of female politicians, the kind of policies they were associated with and how they were evaluated in terms of their performance as political lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…In the study of communication discourses, sentiment analysis has been mostly used for the identification of polarity in discussion in social media such as Twitter (Kumar and Jaiswal 2020) or Facebook (Sandoval-Almazan and Valle-Cruz 2020;Haryanto et al 2019) and has also been employed in characterising the polarity of mainstream media discourses (Boukes et al 2020;Backfried and Shalunts 2016;Padmaja et al 2014;Balahur and Steinberger 2009;Godbole et al 2007). Similarly, studies by Leavy (2019Leavy ( , 2020 and Jia et al (2016) have employed such techniques in the research of media portrayal of women.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of communication discourses, sentiment analysis has been mostly used for the identification of polarity in discussion in social media such as Twitter (Kumar and Jaiswal 2020) or Facebook (Sandoval-Almazan and Valle-Cruz 2020;Haryanto et al 2019) and has also been employed in characterising the polarity of mainstream media discourses (Boukes et al 2020;Backfried and Shalunts 2016;Padmaja et al 2014;Balahur and Steinberger 2009;Godbole et al 2007). Similarly, studies by Leavy (2019Leavy ( , 2020 and Jia et al (2016) have employed such techniques in the research of media portrayal of women.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that female candidates’ support would be increased if they are subjected to gender bias violence. Leavy ( 2019 ) performed a comprehensive study on coverage of male and female politicians in new papers to identify potential gender bias. Toffoletti ( 2007 ) studied the behavior and narrative of stories of violence against women in Australian newspapers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Work in corpus studies in 2019 has also had much to say about issues connected to gender and identity. Leavy (2019) uses a corpus of Irish newspaper coverage of politicians to examine the media portrayal and evaluation of female politicians over a fifteen-year period. Limatius (2019) conducts a corpus analysis of body descriptors in plus-size fashion blogs demonstrating that different descriptors are used by bloggers influenced by ‘fat acceptance activism’ to those used by bloggers focussed on style and trends in fashion.…”
Section: Corpus Approachesmentioning
confidence: 99%